The efficacy of single-dose systemic and single-dose local antifungal therapy in the treatment of vulvovaginal candidiasis (Annals of Medical Research, 2021)
None
Keywords: s : Vulvovaginal candidiasis, fluconazole, isoconazole, ketokonazole